A new faunistical record from Kastamonu (Turkey): Hydrometra stagnorum (Linnaeus, 1758) (Hemiptera: Heteroptera: Hydrometridae) - Küçükbasmacı, İbrahim (Zenodo, 2020)
ABSTRACT:Heteroptera, the majority of which are terrestrial is a worldwide distributed group of insects inhabiting both terrestrial and aquatic habitats and has an important ecological role. The two infraorders, Gerromorpha and Nepomorpha, including the aquatic and semi-aquatic members of the suborder Heteroptera. The members of Hydrometridae family are one of the most distinctive heteropteran groups with their small stick-like insects with an elongate head and exceedingly slender legs. It has been reported 14 taxa from the infraordo Nepomorpha and Gerromorpha in Kastamonu so far. In this study, a new faunistic record is shown for Kastamonu. Also, morphological diagnosis, habitat, distribution in Turkey and Palearctic data of Hydrometra stagnorum (Linnaeus, 1758) (Hemiptera: Heteroptera: Hydrometridae) are given.
Keywords: Heteroptera, Hydrometra stagnorum, new record, Kastamonu, Turkey